Elevated Numbers of HIV-Specific Poly-Functional CD8+ T Cells With Stem Cell-Like and Follicular Homing Phenotypes in HIV-Exposed Seronegative Individuals - Munusamy Ponnan, Sivasankaran; Thiruvengadam, Kannan; Kathirvel, Sujitha; Shankar, Janani; Rajaraman, Akshaya; Mathaiyan, Manikannan; Dinesha, Thongadi Ramesh; Poongulali, Selvamuthu; Saravanan, Shanmugam; Murugavel, Kailapuri Gangatharan; Swaminathan, Soumya; Tripathy, Srikanth Prasad; et al. (Frontiers in Immunology, 2021)
HIV-specific CD8+ T cells are essential for viral control during acute and chronic HIV infection. Although many studies have demonstrated the importance of HIV-specific CD8+ T cells in viral control, the correlation of protection against HIV infection remains incompletely understood. To better understand the nature of the immune responses elicited during the early control of HIV infection, we analyzed the phenotype, distribution, and function of anti-viral CD8+ T cells in a cohort of HIV-exposed seronegative (ESN) women. We compared them with healthy controls and HIV-infected individuals. Besides, we evaluated the in vitro viral inhibition ability of CD8+ T cells against diverse HIV-1 strains. We found that the ESN group had significantly higher levels of CD8+ T cells that express T-stem cell-like (TSCM) and follicular homing (CXCR5+ CD8+ T cells) phenotype with more effector like characteristics as compared to healthy controls. Further, we found that the ESN population had a higher frequency of HIV-specific poly-functional CD8+ T cells with robust in vitro viral inhibiting capacity against the different clades of HIV. Overall, our results demonstrate that the ESN population has elevated levels of HIV-specific poly-functional CD8+ T cell responses with robust virus inhibiting ability and express elevated levels of markers pertaining to TSCM and follicular homing phenotype. These results demonstrate that future vaccine and therapeutic strategies should focus on eliciting such CD8+ T cells for protection against HIV infection and or better viral control.